MyoBio: An automated bioreactor system technology for standardized perfusion-decellularization of whole skeletal muscle - Ritter, Paul; Cai, Aijia; Reischl, Barbara; Fiedler, Maren; Prölß, Gerhard; Frie, Benjamin; Kretzschmar, Elke; Michael, Mena; Hartmann, Kristin; Lesko, Christian; Salti, Hatiham; Arkudas, Andreas; et al. (IEEE transactions on bio-medical engineering, 2022)
Objective: Decellularizing solid organs is a promising top-down process to produce acellular bio-scaffolds for 'de novo' regrowth or application as tissue 'patches' that compensate, e.g., large volumetric muscle loss in reconstructive surgery. Therefore, generating standardized acellular muscle scaffolds marks a pressing area of need. Although animal muscle decellularization protocols were established, those are mostly manually performed and lack defined bioreactor environments and metrologies to assess decellularization quality in real-time. To close this gap, we engineered an automated bioreactor system to provide chemical decellularization solutions to immersed whole rat gastrocnemius medialis muscle through perfusion of the main feeding arteries. Results: Perfusion control is adjustable according to decellularization quality feedback. This was assessed both from (i) ex situ assessment of sarcomeres/nuclei through multiphoton fluorescence and label-free Second Harmonic Generation microscopy and DNA quantification, along with (ii) in situ assessment of the samples passive mechanical elasticity. Conclusion: We find DNA and sarcomere-free constructs after 72 h of 0.1% SDS perfusion-decellularization. Furthermore, passive elasticity can be implemented as additional online decellularization quality measure, noting a threefold elasticity decrease in acellular constructs. Significance: Our MyoBio represents a novel and useful automated bioreactor environment for standardized and controlled generation of acellular whole muscle scaffolds as a valuable source for regenerative medicine.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Biological systems; Biomechatronics; bioreactors; Biotechnology; decellularization; Inductors; Muscles; Plastics; skeletal muscle; Surgery; Tendons; tissue engineering